Tinjauan Literatur: Hubungan Stunting terhadap Keparahan Karies Gigi Sulung dan Kebersihan Rongga Mulut pada Anak Usia Sekolah Dasar - Safira Fasya (Jurnal Syntax Admiration, 2024)
The purpose of this study was to analyze the effect of stunting on the severity of caries of deciduous teeth and the level of oral hygiene in children. Method: the systematic literature review taken from national journals and international journals is used. Results: From 10 selected journals there was a significant correlation between stunting children and the severity of dental caries in children. The effects of stunting in addition to impaired cognitive function also affect the severity of dental caries and oral hygiene. Children with malnutrition have higher dental caries than children with good nutrition. This is due to changes in salivary characteristics and salivary secretions to decrease causing cavities in the oral cavity. Saliva as a cleaning and anti-bacterial agent in the oral cavity. As a result of dental caries that causes pain, interferes with masticatory function and affects nutritional status. Conclusion: From various types of studies it is proven that children with stunting have various impacts on the growth and health condition of their teeth and mouth. It can be seen from the high incidence of caries in children and it is also found that there are changes in conditions in the oral cavity that cause a decrease in the rate of salivary flow.